2012
DOI: 10.1021/jp303579b
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Transport in Polymer Electrolytes Based on PEO and the PMImI Ionic Liquid: Effects of Salt Concentration and Iodine Addition

Abstract: We find a strong impact of ion pairing on ionic transport in potential Grätzel-cell electrolytes based on poly(ethylene oxide) (PEO) and 1-propyl-3-methylimidazolium iodide (PMImI). Furthermore, the addition of free iodine enhances both mass and charge transport, which can be explained by the reduced pair-formation tendency of the bulky triiodide ion. These results arise from conductivity and diffusion measurements on amorphous complexes with EO/PMImI molar ratios of 20 and 30 and their evaluation in a compreh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 32 publications
3
12
1
Order By: Relevance
“…One more interesting observation is that the diffusion parameter measured to be 9 × 10 −8 cm 2 /s and 9.2 × 10 −7 cm 2 /s at the room temperature and 353 K, respectively which by one order of magnitude. The value of diffusion coefficient obtained in the present work is quite comparable to that reported for PEO based ion conducting polymer electrolytes using Nernst−Einstein equation [81]. From Nernst−Einstein, one can convert the conductivity into a diffusion coefficient and vice versa, i.e., the charge diffusivity D σ can be expressed as:Dσ=KBTCsalte2σdc where all parameters except C salt in the relation have usual meanings.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…One more interesting observation is that the diffusion parameter measured to be 9 × 10 −8 cm 2 /s and 9.2 × 10 −7 cm 2 /s at the room temperature and 353 K, respectively which by one order of magnitude. The value of diffusion coefficient obtained in the present work is quite comparable to that reported for PEO based ion conducting polymer electrolytes using Nernst−Einstein equation [81]. From Nernst−Einstein, one can convert the conductivity into a diffusion coefficient and vice versa, i.e., the charge diffusivity D σ can be expressed as:Dσ=KBTCsalte2σdc where all parameters except C salt in the relation have usual meanings.…”
Section: Resultssupporting
confidence: 85%
“…Arya and Sharma, recently studied the electrical conductivity value of particular SPEs films and they found that the conductivity depends on the number of free charge carriers. In their study, the obtained diffusion coefficient of about (≈10 −18 cm 2 /s) for SPEs based on PEO-PVP complexed with NaPF 6 [83] which is very low compared to the values obtained in the current work and that reported by other researchers [81]. Moreover, Sun et al, [84], computed the diffusion coefficient of almost (≈10 −10 cm 2 /s) for poly (trimethylene carbonate) based Li ion conducting electrolyte.…”
Section: Resultscontrasting
confidence: 57%
“…Ion dynamics can be studied by multinuclear dynamic NMR experiments . In particular, spin‐lattice relaxation and diffusion studies are well established in salt‐in‐polymer electrolytes . The relaxation of nuclear spins depends on the spectral density function, which describes dynamic fluctuations of the local environment of a nucleus.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] In particular, spin-lattice relaxation and diffusion studies are well established in saltin-polymer electrolytes. [17][18][19][20][21][22][23][24][25][26] The relaxation of nuclear spins depends on the spectral density function, which describes dynamic fluctuations of the local environment of a nucleus. By determining spin-lattice relaxation rates R 1 and applying appropriate motional models, the local dynamics of a nucleus is characterized by its motional correlation time.…”
Section: Introductionmentioning
confidence: 99%
“…It was previously demonstrated by our group that the highest ionic conductivity for methacrylate SICs can be achieved by copolymerization of Li‐ion‐containing monomers with PEGM for [ILM]:[PEGM] molar ratio equal to 1:7.2 . PEGM was chosen due to the presence of oxyethylene fragments in its side chain that, by analogy with poly(ethylene oxide), should improve the solubility of ionic species, facilitate their dissociation and promote an increase in the conductivity of the resultant copolymers. Moreover, copolymerization with PEGM often allows for a decrease in T g of resultant polyelectrolytes, which in its turn affects their ionic conductivity increasing it to a high level .…”
Section: Resultsmentioning
confidence: 99%